Rational Drug Therapy for the Management of Diabetes Mellitus - Fawad Mahmood, Shahid Anwar, Ayesha Javaid, Moiz Inam Khan, Bilal Ahmed, Abad Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetes Mellitus is one of the major worldwide public health issues, along with socio-economic growth. Diabetes Mellitus is a chronic metabolic syndrome of several causes characterized by long-lasting hyperglycemia with the turmoil of carbohydrates. The study aimed to evaluate pharmacotherapy on rational grounds for drug-drug interactions, polypharmacy, and untreated conditions if any., For the recording of patient case histories, a standard questionnaire was designed, which includes age, sex, history, chief complaints, Clinical tests, diagnosis & patient’s family history, etc., the copy of which is appended. Considering 20 cases, different parameters were studied which showed that 17 out of 20 cases received rational therapy according to standard pharmacotherapy and the patients responded well to the prescribed therapy, 3 cases out of 20 received irrational therapy due to which they showed poor response. The percentage of the female patient was 40% and the male patient was 60%. In some of these cases, drug interactions were found and their percentage was 22.1%. The most prominent interaction occurrence was of Ramipril with metformin i.e. 18.75% and Ciprofloxacin interaction with glimepiride is 6.25% etc. In all cases, a total of 86 drugs related problems were reported. The percentage of untreated conditions was 9.3%, drug without indication 6.98%, and cost-related problems were 20.9%, etc. In some cases, concurrent diseases were also found i.e. hypertension at 37.5% and asthma at 25 was prominent. Patients with ages between 41-50 and 51-60 years have a high percentage of Diabetes Mellitus i.e. 40% and 40% respectively. The most prominent ADRs were insomnia, skin rashes, dizziness, nausea, vomiting, diarrhea, etc. Nausea, vomiting, and diarrhea are more frequent with antibiotics. Keywords: Epidemiology, Etiology, Pathophysiology, Investigations, Complications and Treatment of Diabetes Mellitus